2004
DOI: 10.1007/s10692-005-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure of flax cellulose induced by solutions of lithium, sodium, and potassium hydroxides

Abstract: In the reaction of cellulose-containing flax material with aqueous solutions of LiOH, NaOH, and KOH, the degree of swelling, sorption of water and alkali, parameters of the crystal lattice formed by alkali cellulose, degree of removal of lignin, and change in the degree of polymerization are a function of the type of cation. For the sorption characteristics and crystal lattice parameters of alkali cellulose, this dependence is determined by the change in the structure of the first and second hydrate shells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Nakano [24,25], Ishikura and Nakano [26], and Tanimoto and Nakano [27,28] reported changes in the dimensional and mechanical properties of wood that occurred after treatment with NaOH-water solution; they attributed these changes to morphological changes in the microfibrils in the wood cell walls. Their results were later confirmed by Voronova et al [29] and Ray and Sarkar [30]. Although many studies concerning treatments of wood and cellulose with NaOH-water solution have been reported, a quantitative description of the morphological changes of the microfibrils and fibers after treatment, particularly with respect to conformational changes, has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 70%
“…Nakano [24,25], Ishikura and Nakano [26], and Tanimoto and Nakano [27,28] reported changes in the dimensional and mechanical properties of wood that occurred after treatment with NaOH-water solution; they attributed these changes to morphological changes in the microfibrils in the wood cell walls. Their results were later confirmed by Voronova et al [29] and Ray and Sarkar [30]. Although many studies concerning treatments of wood and cellulose with NaOH-water solution have been reported, a quantitative description of the morphological changes of the microfibrils and fibers after treatment, particularly with respect to conformational changes, has not been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 70%
“…The initial increase in cellulose swelling with increasing alkali concentration results from the second factor being predominant at lower alkali concentrations, while the decrease in cellulose swelling at higher alkali concentrations results from a predominance of the first factor. The lower SRV in KOH treatments, as compared to NaOH treatments, is attributed to the smaller hydration radius of K + ions in comparison to that of Na + ions (Kielland 1937;Voronova et al 2004).…”
Section: Solution Retention Valuesmentioning
confidence: 95%